Additive effect of in-hospital TIMI bleeding and chronic kidney disease on 1-year cardiovascular events in patients with acute coronary syndrome: Data from Taiwan Acute Coronary Syndrome Full Spectrum Registry - Lin, Tsung-Hsien (Heart Vessels, 2014)
In-hospital bleeding (IHB) is associated with the risk of subsequent cardiovascular events (CVE) in acute coronary syndrome (ACS). We investigated whether increased risk of CVE by IHB is influenced by chronic kidney disease (CKD) or both have detrimental effects on CVE. In a Taiwan national-wide registry, 2819 ACS patients were enrolled. CKD is defined as an estimated glomerular filtration rate of <60 ml/min per 1.73 m(2). The primary end point is the composite of death, non-fatal myocardial infarction and non-fatal stroke at 12 months. 53 (1.88 %) and 949 (33.7 %) patients suffered from IHB and CKD, respectively. Both IHB and CKD are independently associated with increased risk of the primary end point (HR 2.04, 95 % CI 1.05–3.99, p = 0.037 and HR 2.17, 95 % CI 1.63–2.87, p < 0.01, respectively). The Kaplan–Meier curves show significantly higher event rates among those with IHB and CKD in the whole, ST-elevation and non-ST elevation populations (all p < 0.01). Patients with IHB(+)/CKD(−), IHB(−)/CKD(+) and IHB(+)/CKD(+) have 1.88-, 2.13- and 2.98-fold risk to suffer from the primary end point compared with those without IHB and CKD (p = 0.23, <0.01 and <0.01, respectively). IHB or CKD is independently associated with poor cardiovascular outcome and patients with both IHB and CKD have the worst outcome in ACS.